Computational and Biological Comparisons of Plant Steroids as Modulators of Inflammation through Interacting with Glucocorticoid Receptor - Mohamed A. Morsy; Snehal S. Patel; Azza A. K. El-Sheikh; Jignasa K. Savjani; Anroop B. Nair; Jigar N. Shah; Katharigatta N. Venugopala (Hindawi Limited, 2019)
Despite the usefulness of glucocorticoids, they may cause hazardous side effects that limit their use. Searching for compounds that are as equally efficient as glucocorticoids, but with less side effects, the current study compared plant steroids, namely, glycyrrhetinic acid, guggulsterone, boswellic acid, withaferin A, and diosgenin with the classical glucocorticoid, fluticasone. This was approached both in silico using molecular docking against glucocorticoid receptor (GR) and in vivo in two different animal models. All tested compounds interacted with GR, but only boswellic acid and withaferin A showed docking results comparable to fluticasone, as well as similar in vivo anti-inflammatory effects, by significantly decreasing serum levels of interleukin-6 and tumor necrosis factor-α in cotton pellet-induced granuloma in rats. In addition, both compounds significantly decreased the percent of change in ear weight in croton oil-induced ear edema in mice and the granuloma weight in cotton pellet-induced granuloma in rats, to levels comparable to that of fluticasone. Both boswellic acid and withaferin A had no effect on adrenal index, but only withaferin A significantly increased the thymus index. In conclusion, boswellic acid may have comparable anti-inflammatory effects to fluticasone with fewer side effects.